Analytical determination of heroin, fentanyl and fentalogues using high-performance liquid chromatography with diode array and amperometric detection. Issue 8 (29th January 2019) - Elbardisy, Hadil M.; Foster, Christopher W.; Cumba, Loanda; Antonides, Lysbeth H.; Gilbert, Nicolas; Schofield, Christopher J.; Belal, Tarek S.; Talaat, Wael; Sutcliffe, Oliver B.; Daabees, Hoda G.; Banks, Craig E.
Abstract : We report a combination of HPLC and electrochemistry towards the detection of heroin, fentanyl and ten fentalogues. Abstract : Over recent years there has been a progressive increase in the adulteration of common illicit street drugs, such as heroin and cocaine, with fentanyl and its derivatives (fentalogues) being the cause of over doses ending with fatal repercussions. Consequently, there is a need for the development of sensitive, selective and reliable analytical protocols for their separation and quantification. Herein, we report for the first time, a combination of high-performance liquid chromatography with a dual-diode array and electrochemical (amperometric) detector achieved for the simultaneous detection and quantification of heroin (HRN), fentanyl and ten fentalogues; the amperometric detection is achieved using a commercially available impinging jet flow-cell that incorporates in-house screen-printed graphite macroelectrodes (SPEs). Both protocols are analytically compared and contrasted in terms of their experimental parameters and chromatographic conditions with the separation and quantification being optimized, with these protocols demonstrating a high sensitivity and reproducibility. The proposed methods were successfully applied for the analysis of the investigated drugs of abuse, in the presence of common adulterants ( e.g. caffeine, paracetamol and benzocaine), co-formulated excipients (starch, lactose, aerosil 200, etc. ) and simultaneously within seized street samples.